Clinical Study of Cranioplasty Combined With Ipsilateral Ventriculoperitoneal Shunt in the Treatment of Skull Defects With Hydrocephalus. Issue 1 (January 2022) - Yan, Zhengcun; Zhang, Hengzhu; Zhang, Zhen; Wang, Xiaodong; Wei, Min; Wang, Xingdong
Abstract : Objective: To explore the clinical effect and safety of cranioplasty combined with ipsilateral ventriculoperitoneal shunts in the treatment of skull defects with hydrocephalus. Methods: The clinical data of 78 patients with skull defects with hydrocephalus were analyzed retrospectively. All patients were treated with cranioplasty and ventriculoperitoneal shunts in 1 stage, including 35 cases of cranioplasty combined with ipsilateral ventriculoperitoneal shunts (ipsilateral operation group) and 43 cases of contralateral operations (contralateral operation group). Results: The incision length (28.97 ± 4.55 cm), operation time (139.00 ± 42.27 minutes), and intraoperative hemorrhage (174.57 ± 79.35 mL) in the ipsilateral operation group were significantly better than those in the contralateral operation group (respectively they were 37.15 ± 5.83 cm, 214.07 ± 34.35 minutes, and 257.21 ± 72.02 mL), and the difference was statistically significant ( t  = 6.786, 8.656, and 4.815, all P  < 0.05). The degree of postoperative hydrocephalus was significantly improved in both groups, but there was no statistically significant difference in the degree of hydrocephalus between the 2 groups ( P  > 0.05). Among the postoperative complications, there was no statistically significant difference in infection, epilepsy, subdural effusion, titanium plate effusion, or excessive cerebrospinal fluid drainage between the 2 groups ( P  > 0.05), but the incidence of intracranial hemorrhage in the ipsilateral operation group (2.86%) was significantly lower than that in the contralateral operation group (20.93%, χ 2  = 4.138, P  = 0.042). The postoperative Glasgow Coma Scale scores of the 2 groups were improved compared with those before the operation ( P  < 0.05), and there was no statistically significant difference in the postoperative Glasgow Coma Scale scores ( P  > 0.05). At 6 months after surgery, there was no statistically significant difference in Glasgow Outcome Scale effectiveness between the 2 groups ( χ 2  = 0.005, P  = 0.944). Conclusions: Cranioplasty combined with ipsilateral ventriculoperitoneal shunt has the same therapeutic effect as a contralateral operation, but it has the advantage of a short operation time, less intraoperative trauma, less bleeding, and less risk of intracranial hemorrhage, which is suitable for clinical applications. Abstract : Supplemental Digital Content is available in the text